An analysis of micronutrient trace elements in children dependent on various modes of feedings (Asian Journal of Pharmaceutical and Health Sciences, 2015)
Micronutrient trace elements Zinc, Iron & Copper among 100 children's, dependent on various feeding methods, randomly selected from various parts of District Bannu, KhyberPakhtunkhwa, Pakistan were determined by Atomic Absorption Spectrometer. Out of 100 children, 64 were male and 36 were female. The serum Zinc, Iron and Copper contents among male children's were 65.38 ±1.7 µg/dl, 64.69 ±2.2 µg/dl and 113.35 ±3.2 µg/dl and among female children were 59.09 ±2.4 µg/dl, 54.23 ±2.4 µg/dl and 123.23 ±5.2 µg/dl respectively, showing significant differences (p
Keywords: Breast & bottle feeding; Micronutrient trace elements; Pakistani population